El Talento Lúdico en el Desarrollo Expresivo en los Niños y Niñas de 4 a 5 años del Centro de Educación Inicial “Diego Donoso”, del Cantón Chambo, durante el año lectivo 2015-2016. - Noboa Zavala, Mary Cruz (2016)
Research is the principle of all inquiry as it allows to establish the causes and effects of the problems that arise as playful expressive talent development of children 4-5 years Early Education Center "Diego Donoso”, the Chambo Canton, period 2015-2016, for which the following general objective arises: to determine the importance of playful expressive talent development in children, and specific objectives. Demonstrate the importance of playfulness talent expressive development, learn about the playful talent expressive development and propose activities of playful talent expressive development in children 4 to 5 years of the Center for Early Education "Diego Donoso" Canton Chambo, 2015-2016.Lo period that was articulated with the theoretical framework to investigate issues such as the playful talent, also with development of expression, to support this research work, reaching methodological framework using inductive deductive method, this method studies the characteristics that have been reflected in the process of expressive development of children aged 4-5 years, this technique of observation was applied, the instrument was used, the tab group observation to gather information on the variables, the Lúdico Talent Development Expressive, where the relevant research study very clearly determined. In a population of 20 children, analyzing and interpreting the results of observation to finally reach the conclusions and recommendations that reflect the importance of leisure skills possessed by infants, to coordinate movements with the expression of their feelings and emotions have to practice recreational or leisure activities as it is known in the educational field.